KEADILAN SEBAGAI PEMECAH MASALAH KONFLIK ANTARA KEKUASAAN (POWER) DAN HAK KEPEMILIKAN (PROPERTY RIGHT) DALAM NEGARA DEMOKRASI (Sebuah Tinjauan Filsafat) - Sihol Farida Tambunan (Jurnal Masyarakat dan Budaya, 2008)
English philosophers such as Thomas Hobbes and John Locke, and the French thinker, Jean Jacques Rousseau had developed philosophical thought about democracy in the beginning of 18th century. Their thoughts to abolish the absolutism of the state and the government have influenced a lot of people, because absolutism is not suitable for the machienary era after the industrial revolution. On the contrary the state must guard the property right of the people according to the contract social based on the constitution. But for most of the under-developed countries, empirical evidences show that democracy is still an idea. The government gives their first priority to develop their countries rather than to grow the welfare of their people. On the contrary, people must sacrifice by giving up their properties such as their ancestor land, forest and river for the sake of development due to the government’s plan. As a consequence, the conflict between the power of the state and the property right of the people cannot be prevented. This article views the problem of conflicting interest through the theory of Justice from Aristoteles, Thomas Aquino and John Rawls is suitable to face the increase of such contemporary problem.